2016
DOI: 10.2352/issn.2470-1173.2016.5.sda-437
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Remote Vision System Aerial Refueling Visual Performance

Abstract: The performance and comfort of aircrew using stereoscopic displays viewed at a near distance over long periods of time are now important operational factors to consider with the introduction of aerial refueling tankers using remote vision system technology. Due to concern that the current U.S. Air Force vision standards and test procedures may not be adequate for accurately identifying aircrew medically fit to operate this new technology for long mission durations, we investigated performance with the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…The advantage provided by stereopsis, that is, the difference in slope under binocular relative to monocular viewing in the grid condition, was similar for undergraduate observers and aircrew (Figure 5). These results are consistent with Deas et al (2017) and studies that have shown improved accuracy of distance judgments in the presence of stereopsis relative to monocular viewing in immersive stereoscopic simulations of aerial refueling (Lloyd & Nigus, 2012;Winterbottom et al, 2016) and helicopter landing tasks (Winterbottom et al, 2017). The pattern of overestimation at near and underestimation at far distances seen in the grid terrain is consistent with observers' reliance on a highly variable vergence signal to scale depth from binocular disparity in the absence of other monocular cues to distance (Foley, 1980).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The advantage provided by stereopsis, that is, the difference in slope under binocular relative to monocular viewing in the grid condition, was similar for undergraduate observers and aircrew (Figure 5). These results are consistent with Deas et al (2017) and studies that have shown improved accuracy of distance judgments in the presence of stereopsis relative to monocular viewing in immersive stereoscopic simulations of aerial refueling (Lloyd & Nigus, 2012;Winterbottom et al, 2016) and helicopter landing tasks (Winterbottom et al, 2017). The pattern of overestimation at near and underestimation at far distances seen in the grid terrain is consistent with observers' reliance on a highly variable vergence signal to scale depth from binocular disparity in the absence of other monocular cues to distance (Foley, 1980).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Lloyd and Nigus (2012) used a stereoscopic aerial refueling simulation to show that observers were more accurate when estimating relative distance with stereopsis, compared with performance without stereopsis. Others have shown improvements in similar tasks that correlate with stereoscopic acuity (Winterbottom, Lloyd, Gaska, Wright, & Hadley, 2016). We showed previously that the presence of stereopsis improved the accuracy of altitude judgments for simulated imagery depicting a low hover flight operation (Deas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although all observers were screened for normal vision using a standard Optec vision tester, ongoing research at USAFSAM has demonstrated that standard pass/fail screening tests may not be adequate. For example, an Observer individual may pass the Optec stereo acuity test with 25 arcsec or better but may nonetheless demonstrate poor stereo acuity when tested with a more accurate threshold level test 33,34 . Figure 8 shows that duration thresholds varied by a factor of about 4 to 1 across observers in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous RVS research showed that several computer-based vision tests were predictive of simulated RVS refueling performance (stereo acuity, contrast sensitivity) while standard USAF tests generally were not [1][2]. This research also showed that measures of ocular alignment were correlated with simulated RVS refueling performance and reported discomfort.…”
Section: Introductionmentioning
confidence: 65%